The impact of the Ukraine crisis on the global vegetable oil market - Glauber, Joseph W.; Laborde Debucquet, David; Mamun, Abdullah (International Food Policy Research Institute, 2023)
The war in Ukraine has pushed prices of agricultural products to historically high levels, and concerns about global food security occupy headlines and world leaders’ minds, as demonstrated by recent International Monetary Fund and World Bank meetings. So far, much of the attention has focused on grains, particularly wheat — because of its importance in diets, and the predicament of countries where wheat accounts for a large share of calories consumed, is largely imported, and is dominated by supplies from the Black Sea. Here, we focus on another important emerging food security issue: The war’s impact on vegetable oils. The Black Sea countries are large exporters of sunflower oil, and the crisis has pushed vegetable oil prices significantly higher, and also triggered trade policy responses around the world that further restrict supplies and raise prices. This post examines the unfolding impacts on the global market for vegetable oils, including additional factors affecting prices such as biofuel policies and export restrictions in the Black Sea and elsewhere.